Peran Sistem Informasi Akuntansi dalam Mempengaruhi Kinerja dan Efektivitas Karyawan dalam Perusahaan - Anggraeni Pratama Indrianto; Ningsih; Duta Arief Christanto; Tilly Raycitra Widya (Jurnal Ilmiah Cano Ekonomos, 2024)
This article discusses the role of Accounting Information Systems (AIS) in influencing employee performance and effectiveness in a company. With advances in technology, AIS has become an integral part of modern organizations. AIS is not only a tool for recording financial transactions, but also provides strategic information that supports managerial decision making. Effective employees are considered key to a company's success, but the challenge of managing their performance and effectiveness is increasingly complex in a rapidly changing business environment. Through AIS, employees can easily access the information needed for their tasks, and influence their motivation and job satisfaction. This study adopts a literature review approach to investigate the role of AIS in the context of employee performance and effectiveness. Through a synthesis of recent findings, this article concludes that quality AIS implementation can have a positive impact on employee performance, depending on the system's ability to provide clear guidance to users. Therefore, companies need to ensure that the AIS they implement meets certain quality standards to ensure effective employee performance improvement in today's competitive business environment. Further research is needed to understand more deeply the relationship between AIS and employee performance and identify factors that influence the implementation and adoption of AIS in organizations.